2003
DOI: 10.1126/science.1085405
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Neuroepithelial Patched-Induced Apoptosis by Sonic Hedgehog

Abstract: During early development in vertebrates, Sonic hedgehog (Shh) is produced by the notochord and the floor plate. A ventrodorsal gradient of Shh directs ventrodorsal patterning of the neural tube. However, Shh is also required for the survival of neuroepithelial cells. We show that Patched (Ptc) induces apoptotic cell death unless its ligand Shh is present to block the signal. Moreover, the blockade of Ptc-induced cell death partly rescues the chick spinal cord defect provoked by Shh deprivation. Thus, the proap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
284
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 289 publications
(307 citation statements)
references
References 27 publications
19
284
1
2
Order By: Relevance
“…In the non-canonical Shh signaling engaged by Ptch1, Ptch1 is shown to independently induce human embryonic kidney 293T cells apoptosis provoked by Shh deprivation (Thibert et al, 2003). However, overexpression of Smo could not protect against cell death.…”
Section: Sonic Hedgehog Signaling: Components Routes and Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…In the non-canonical Shh signaling engaged by Ptch1, Ptch1 is shown to independently induce human embryonic kidney 293T cells apoptosis provoked by Shh deprivation (Thibert et al, 2003). However, overexpression of Smo could not protect against cell death.…”
Section: Sonic Hedgehog Signaling: Components Routes and Mechanismmentioning
confidence: 99%
“…In addition, Ptch1 undergoes proteolytic processing at the C-terminus and the soluble C-terminal domain (CTD) translocates to the nucleus and mediates a new form of signal transduction (Kagawa et al, 2011). Different from Drosophila (Johnson et al, 2000), the CTD is not required for the canonical signal transduction but most likely has a distinct function in apoptosis and/or proliferation in mammals (Makino et al, 2001; Nieuwenhuis et al, 2007; Thibert et al, 2003). Besides apoptosis, exogenous Ptch1 in 293T cells induces the redistribution of cyclin B1 from the nucleus to the cytoplasm, resulting in reduced cell proliferation.…”
Section: Sonic Hedgehog Signaling: Components Routes and Mechanismmentioning
confidence: 99%
“…In addition to its morphogen activity, Shh was also shown to be a survival factor: indeed, Le Douarin and colleagues discovered that experimental withdrawal of Shh in chick embryos by partial destruction of the notochord leads to massive cell death in the developing neural tube (Charrier et al, 1999(Charrier et al, , 2001. It was subsequently demonstrated that Shh functions as a survival factor by inhibiting the apoptotic function of Ptc (Thibert et al, 2003). Thus, Ptc is a DR and can signal independently of Smo.…”
Section: Dependence Receptors: a Short Historymentioning
confidence: 99%
“…Receptor cleavage is important for apoptotic function, as mutation of the cleavage site abolishes cell death induction. DCC, neogenin, Ptc, ALK, EphA4 are cleaved once, roughly in the middle of their intracellular domain (Mehlen et al, 1998;Thibert et al, 2003;Matsunaga et al, 2004;Mourali et al, 2006;Furne et al, 2009). The cleavage site of UNC5 receptors is very close to the plasma membrane (Llambi et al, 2001), whereas RET, Trkc and MET have two cleavage sites A new paradigm in cell signaling and cancer therapy D Goldschneider and P Mehlen (Bordeaux et al, 2000;Foveau et al, 2007;TauszigDelamasure et al, 2007).…”
Section: Drs Are Caspase Substratesmentioning
confidence: 99%
See 1 more Smart Citation